Correlation of Coagulation Parameters With Clinical Outcomes During the Coronavirus-19 Surge in New York: Observational Cohort - Reyes Gil, Morayma; Gonzalez-Lugo, Jesus D.; Rahman, Shafia; Barouqa, Mohammad; Szymanski, James; Ikemura, Kenji; Lo, Yungtai; Billett, Henny H. (Frontiers in Physiology, 2021)
Importance COVID-19 has caused a worldwide illness and New York became the epicenter of COVID-19 in the United States from Mid-March to May 2020. Objective To investigate the coagulopathic presentation of COVID and its natural course during the early stages of the COVID-19 surge in New York. To investigate whether hematologic and coagulation parameters can be used to assess illness severity and death. Design Retrospective case study of positive COVID inpatients between March 20, 2020-March 31, 2020. Setting Montefiore Health System main hospital, Moses, a large tertiary care center in the Bronx. Participants Adult inpatients with positive COVID tests hospitalized at MHS. Exposure (for observational studies) Datasets of participants were queried for demographic (age, sex, socioeconomic status, and self-reported race and/or ethnicity), clinical and laboratory data. Main Outcome and Measures Relationship and predictive value of measured parameters to mortality and illness severity. Results Of the 225 in this case review, 75 died during hospitalization while 150 were discharged home. Only the admission PT, absolute neutrophil count (ANC) and first D-Dimer could significantly differentiate those who were discharged alive and those who died. Logistic regression analysis shows increased odds ratio for mortality by first D-Dimer within 48 hrs. of admission. The optimal cut-point for the initial D-Dimer to predict mortality was found to be 2.1 μg/mL. 15% of discharged patients required readmission and more than a third of readmitted patients died (5% of all initially discharged). Conclusion We describe here a comprehensive assessment of hematologic and coagulation parameters in COVID-19 and examine the relationship of these to mortality. We demonstrate that both initial and maximum D-Dimer values are biomarkers that can be used for survival assessments. Furthermore, D-Dimer may be useful to follow up discharged patients.